Efektivitas metode kolaboratif dalam pembelajaran menulis - Wijayanti, Sri Hapsari (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
This study aims to describe how the subjects performed the editing steps and to examine whether the collaborative writing method, as part of the academic writing process—specifically the editing stage—can be used by lecturers to teach Bahasa Indonesia at the university level. Unlike previous studies, this research focuses on differences between men’s and women’s preferences in using collaborative writing. Based on data from sixty participants from the Faculty of Economics at Atma Jaya Catholic University Jakarta, this study employed a quasi-experimental design. Data were collected through essay writing tests, questionnaires, and in-depth interviews. The findings show that collaborative writing is perceived as interesting, useful, and not boring. Male students were found to prefer this method more than female students.